Algumas técnicas de construção de alguns poliedros e suas aplicações no ensino - Carneiro Júnior, Mário Pinto [UNESP] (2014)
The aim of this dissertation is exploring some teaching solid geometry possibilities starting from models of regular convex polyhedra and of prisms and pyramids, for which we introduce some construction techniques using materials accessible and easy to manipulate, such as paper, plastic sheet, metal and wooden rods, magnets, steel balls, among others. The geometric solids thus constructed can be applied in primary and secondary schools as support material, recreation or curiosities, or as motivation for investigating properties of these solids, could say that some of these are indicated constructs a didactic innovation. Assemblies and suggested applications meet the educational principles presented in the National Curricular Parameters. These techniques can be easily applied to other polyhedra we wish to work in teaching